2017
DOI: 10.1038/srep46546
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria in gastrostomy fed patients with cystic fibrosis

Abstract: Multi-drug resistant Mycobacterium abscessus complex (MABSC) is a form of Nontuberculous mycobacteria (NTM) of special, international concern in Cystic Fibrosis (CF). We hypothesised that gastric juice and percutaneous endoscopic gastrostomy (PEG) feeding devices might yield MABSC isolates. Gastric juice and sputa from sixteen adult PEG fed CF patients and five replaced PEG tubes were studied. Bacterial and fungal isolates were cultured. Mycobacterium were identified by rpoB, sodA and hsp65 gene sequencing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…It is known for being responsible for a wide spectrum of diseases related to skin and soft tissues, peritonitis, central nervous system infections and bacteremia in humans [18]. Interestingly, presence of this NTM in gastric juice was recently reported among cystic fibrosis patients [19]. Here, using various techniques like culture, 16S rRNA gene sequencing, hsp65 gene sequencing, erm (41) gene PCR, acid-fast staining, immunohistochemistry and immunofluorescence we report that the infection of M .…”
Section: Discussionmentioning
confidence: 99%
“…It is known for being responsible for a wide spectrum of diseases related to skin and soft tissues, peritonitis, central nervous system infections and bacteremia in humans [18]. Interestingly, presence of this NTM in gastric juice was recently reported among cystic fibrosis patients [19]. Here, using various techniques like culture, 16S rRNA gene sequencing, hsp65 gene sequencing, erm (41) gene PCR, acid-fast staining, immunohistochemistry and immunofluorescence we report that the infection of M .…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85] A few studies have explored the relationship between NTM PD and gastroesophageal reflex disease (GERD). 86,87 NTM are readily found in the water we ingest and they are able to survive in a low pH environment. Additionally, in the lungs they persist in an intracellular compartment.…”
Section: Risk Factors Associated With Ntm Pulmonary Diseasementioning
confidence: 99%
“…It has also been reported that the increase of medical tourism among US citizens has led to the increase of NTM infections from cosmetic surgery performed in other countries [22]. Multi-drug resistant Mycobacterium abscessus complex has become a concern as the cause of infection in Cystic Fibrosis [23].…”
Section: Infection By M Tuberculosis Infection By Ntm Is Not Transmmentioning
confidence: 99%